Resposta :
Explicação passo-a-passo:
e
(V12 * V15 )/ V8
( V( 12 * 15 )/ V8
( V180 )/V8 =
180 =2² *3² * 5¹
8 = 2² * 2¹
reescrevendo
[ V(2² * 3² * 5¹ ) / V(2² * 2¹ )
2 * 3 V5 / 2 V2
6V5 / 2V2 =
por 2
3V5/1V2 >>>resposta
f
[³V9 * ³V10 ] / [ ³V12 * ³V15 ]
9 * 10 = 90
12 * 15 = 180
reescrevendo
[ ³V90 ] / ³V180 ]
90 / 180 ( por 90 ) = 1/2 >>>>
³ V(1/2) >>>> resposta
g
(^6√4 x √³√10 )/ ( ^6V120)
√³√10 = multiplica os indices >>> 3 * 2 = 6
reescrevendo
(^6V4 * ^6V10 ) / ( ^6V120 )
^6V4 * 10) / ^6V120
^6V40 / ^6V120
40 : 120 = por 40 = 1/3 >>>
resposta
^6V(1/3)